Antibody levels and parasitemia of anaplasma marginale of nellore and ibagé calves and nellore crossbreds, in an enzootic area - Madruga, C. R.; Kessler, Raul H.; Gomes, A.; Schenk, M. A.M.; Andrade, D. F. de (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out to determine the dynamics of Anaplasma marginale infection of Nellore and Ibagé calves and of the following crossbred calves:Nellore x Fleckvieh, Nellore x Chianina and Nellore x Charolais in the homogeneal microrregion of Campo Grande, State of Mato Grosso do Sul, Brazil. A positive relation was observed between serum immunoglobulins in the dams and colostral immunoglobulins in the calves. This relation expressed the colostral transmission of antibodies. The proportion of serologically negative calves increased in the 30th day of life, and reached the peak at the 60th day in most of the experimental groups. The parasitemia was first detected at 30 days of age and reached a peak at 90 days. These results showed that the humoral immunity against A. marginale was an important component of the natural resistance complex and that there is a critical period around 60 days after birth, of increased probability of occurrence of anaplasmosis. Finally, the Ibagé calves when compared with Nellore calves and crossbreds with half-blood Nellore showed a higher meam parasitemia, statistically significant (P < 0.05) indicating that the Nellore breed and its crossbreds are more suitable to the region due to a smaller probability of Anaplasmosis occurrence.